2017
DOI: 10.17221/428/2016-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Some physiochemical properties of Acacia honey from different altitudes of the Asir Region in Southern Saudi Arabia

Abstract: The physiochemical properties of six Acacia honey samples taken from three different altitudes in the Asir region were determined. The means of all the studied parameters were within the international standards and were comparable to previous studies (0.11 ± 0.08% for ash, 10.93 ± 1.97% for water, 3.56 ± 0.19 for pH, 38.63 ± 17.17 meq/kg <br /> for acidity, 659.51 ± 324.98 μS/cm for conductivity, and 1.45 ± 0.02 for specific gravity). Comparison of the mean values of the parameters at the different altit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 12 publications
5
7
0
Order By: Relevance
“…The lowest average specific gravity was measured in acacia honey (1.430 g/cm 3 ), while the highest one (of 1.435 g/cm 3 ) was measured in linden samples. Quite close values, between 1.426 and 1.440 g/cm 3 , were found by Attri [50] in Indian honey and between 1.42 and 1.46 g/cm 3 by Ahamed et al [18] in honey from Saudi Arabia. Lower values were found, 1.40 g/cm, by [49] in Indian raw honey.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The lowest average specific gravity was measured in acacia honey (1.430 g/cm 3 ), while the highest one (of 1.435 g/cm 3 ) was measured in linden samples. Quite close values, between 1.426 and 1.440 g/cm 3 , were found by Attri [50] in Indian honey and between 1.42 and 1.46 g/cm 3 by Ahamed et al [18] in honey from Saudi Arabia. Lower values were found, 1.40 g/cm, by [49] in Indian raw honey.…”
Section: Discussionsupporting
confidence: 67%
“…The gravimetric method was applied to assess the raw honey specific gravity, using the pycnometer device. Values were obtained by dividing the pycnometer mass (bottle of 50 mL) filled with honey by the mass of the same bottle, filled with distilled water [18,19].…”
Section: Specific Gravitymentioning
confidence: 99%
“…Moisture content of both samples are similar to some local Indonesian honey reported (Adalina, 2018;Evahelda, Pratama, Malahayati, & Santoso, 2017;Savitri, Hastuti, & Suedy, 2017) and Indian honey which ranged from 22.6-26.2% w/w (Kavapurayil et al, 2014). The values obtained in this study were higher than rubber honey and rambutan honey from Indonesia (Harjo, Radiati, & Rosyidi, 2015), Nigerian honey (Buba et al, 2013), Algerian honey (Khalil et al, 2012), Saudi Arabia honey (Mohammed et al, 2017), and Pakistan honey (Ahmed et al, 2016).…”
Section: Proximate Analysis Bsupporting
confidence: 82%
“…Concerning the effect of altitude on the physicochemical properties of honey, some previous studies reported the effect of altitude on some physicochemical properties honey such as the pH, conductivity, moisture, speci c gravity and acidity (Popov-Raljića et al, 2015;Mohammed et al, 2017). In a previous study, We have reported that the altitude signi cantly affected the concnetration of vitamin C in Acacia and Ziziphus honey samples in different harvesting season (Al-Mosa et al, 2019).…”
Section: Discussionmentioning
confidence: 83%